Vitamin D in Parkinson's disease: A systematic review of randomized controlled trials - Paraskevi Detopoulou; Gavriela Voulgaridou; Alexandra Saridaki; Ioanna Pylarinou; Elissaios-Minos Argyris; Vasilios Dedes; Constantinos Giaginis; Georgios I. Panoutsopoulos; Sousana K. Papadopoulou (Clinical Nutrition Open Science, 2023)
Summary: In recent years, neurodegenerative diseases are a leading cause of morbidity and disability worldwide, with Parkinson's disease (PD) being the most prevalent. Although diet and vitamin status play a crucial role in PD, the results of vitamin D supplementation are scarce and contradictory. Therefore, the present systematic work reviewed the available randomized controlled trials (RCTs) regarding the role of vitamin D supplementation in patients with PD in the Pubmed, Scopus and Cochrane databases and in grey literature. Four RCTs including 321 patients with PD were identified. Various doses of vitamin D were administered (1,000–10,000 IU/d) and different exposure outcomes were assessed. One study reported beneficial effects of vitamin D on the Hoehn and Yahr scale (HY) and two studies reported null effects on the Unified Parkinson's Disease Rating Scale (UPDRS). Regarding functional tests, heterogeneous results in the timed-up and go (TUG) test were observed in two studies. One study conducted minute walking tests at 6 and 10 minutes and found an improvement only in the 6MWT. In conclusion, a very small number of RCTs have assessed the effects of vitamin D supplementation on PD. Some isolated beneficial effects of vitamin D were reported on functional scales and tests but more studies are needed to draw safe conclusions regarding its supplementation in PD.